Interactions between krill and its predators in the western Ross Sea - De Felice, Andrea; Biagiotti, Ilaria; Costantini, Ilaria; Canduci, Giovanni; Leonori, Iole (Frontiers in Marine Science, 2024)
Krill is a fundamental resource in the pelagic food web of the Ross Sea, constituting an important link between primary production and top predators. A series of Italian research voyages to the Ross Sea from 1994 to 2016 have contributed to our understanding of the dynamics of krill populations inhabiting the Ross Sea. Only the surveys in 1994 and 2004 reported information on krill’s predators through visual census data, and 2004 data were not object of publication until now. Analyzing Euphausia superba and Euphausia crystallorophias abundance spatial distribution in the study area in relation to the distribution of its key natural predators have shown a significant relationship between the spatial distribution of minke whales’ abundance and the density of E. superba biomass, indicating a classical predator-prey interaction. Moreover, krill biomass density data in the water column were analyzed together with the main environmental data from CTD samplings. The analysis of krill density data in relation to environmental factors throughout the water column revealed a significant relation between E. superba abundance and salinity, a result that may be linked to the presence of ice melting effects improving environment productivity conditions.